Prevalence of International Medical Graduates in Integrated Plastic Surgery Programs - Denisse Cristina Porras Fimbres, BS; Steven Zeng, BA; Brett Thomas Phillips, MD, MBA (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. International medical graduates (IMGs) are physicians who did not attend medical school in the USA or Canada. IMGs comprise nearly one-quarter of the physician workforce and play a vital role in health care. Here, we aimed to identify the prevalence of IMGs in integrated programs and evaluate factors that influence their success in the residency match. Methods:. The annual match reports from 2010 to 2020 were retrieved and summarized. Electronic surveys for program directors and program coordinators were distributed to US integrated plastic surgery programs. Each program’s website was appraised for information regarding the eligibility of IMGs. Websites were also used to identify the number of IMG residents. Results:. The number of applicants who matched into integrated programs ranged from 69 to 180 per year, of which US applicants comprised 61–165. US IMGs filled one to three positions per year, whereas non-US IMGs filled two to seven. Although 48% of programs have matched non-citizen IMGs and 79% have not encountered difficulties during the visa process, 67% of coordinators reported that the onboarding process is more challenging for IMGs. There are no IMGs in 52% of programs, and most institutions offer information on their website regarding visa sponsorship. Conclusion:. IMGs make up less than 10% of filled positions per cycle. Although most programs accept IMGs, a small number matriculate. This may be explained by the competitiveness of integrated programs and the volume of IMG applications. Further research is needed to identify contributing factors of low IMG representation in plastic surgery programs.